Probability with applications in R - Dobrow, Robert P. (John Wiley & Sons, Inc., 2014)
"A good probability book at the undergraduate level should develop proper problem-solving skills and mathematical maturity; contain a nice mix of theory and application; and be useful in numerous client disciplines (such as computer science, economics, and engineering). It should be written by someone who has consistently taught the course over numerous years and is tolerant of varying levels of student/reader backgrounds. Probability with Applications in R by Robert Dobrow is such a book. Passionate about problem-solving methods and strategies, Dobrow offers guided assistance for techniques that can be generalized to a wide range of situations (e.g. taking complements, working with indicator variables, conditioning, etc.). The author also introduces and then emphasizes simulation (by way of the ever-increasing popularity of freeware R) throughout the text in order to illustrate concepts and highlight computational and theoretical results. Real-life data and examples, over 150 applications, and a multitude of simple and provocative exercises are prevalent. Other key features include discussion of probabilistic topics rather than combinatorial ones; multiple "point-of-view" arguments; and an early introduction to random variables"--